Enhancing Students’ Conceptual Mastery of Mechanics through Smartphone-Based Inquiry Laboratories in Introductory Physics - Alexander Schmidt (Britain International for Academic Research (BIAR) Publisher, 2015)
Introductory physics courses, particularly in mechanics, continue to pose significant conceptual difficulties for first-year University students, largely due to persistent misconceptions related to force, motion, and acceleration. Conventional laboratory instruction often emphasizes procedural verification rather than conceptual reconstruction, limiting its effectiveness in addressing these misconceptions. The integration of smartphone-based laboratories offers a promising, accessible, and cost-efficient alternative that supports inquiry-based learning. This quasi-experimental study examines the effectiveness of smartphone-based laboratories in enhancing students’ conceptual understanding of mechanics. A total of 128 first-year university students participated in the study and were assigned to either an experimental group or a control group. The experimental group engaged in five inquiry-oriented laboratory activities utilizing the phyphox mobile application, while the control group conducted traditional verification-based experiments covering equivalent topics. Students’ conceptual understanding was assessed using the Force Concept Inventory (FCI) administered as both pretest and posttest measures. The findings indicate a statistically significant improvement in the experimental group compared to the control group. Furthermore, students in the smartphone-based laboratory group reported higher levels of engagement, perceived authenticity of experimentation, and stronger connections to real-world contexts. These results demonstrate that smartphone-based laboratories represent an effective pedagogical approach for fostering deeper conceptual understanding in introductory mechanics. The study underscores the potential of mobile technologies to support active, inquiry-driven learning in physics education.